Komitmen Jepang dalam Meredam Kekerasan pada Perempuan Khususnya saat Pandemi Covid-19 bersama United Nations Women (UN Women) - Maharani, Nanda Putri; Mahdi, Imam (Jayapangus Press, 2023)
This research focuses on Japan's commitment to reducing violence against women around the world because the position of women is an important issue in various aspects. Japan in collaboration with UN Women continues to strengthen partnerships to achieve significant changes in women's lives. Japan plays a role in helping women who are struggling against violence by injecting funds into UN Women to implement programs that focus on protecting women's lives and the challenges faced during the Covid-19 pandemic. This article uses the concept of gender mainstreaming which was based on the United Nations Conference in Beijing. This qualitative study aims to examine Japan's commitment to UN Women based on various literatures. This finding will explore how Japan, with a bad image that still lingers, is committed to reducing violence against women in the era of the Covid-19 pandemic with UN Women.